Reimagining Scientific Literacy through a Sasambo-Integrated Scaffolding Inquiry Model - Ferniawan Ferniawan; Agus Ramdani; Joni Rokhmat; A. Wahab Jufri; A. A. Sukarso; Na Jiang (Online Learning In Educational Research (OLER), 2026)
Scientific literacy has become a fundamental competency in higher education, yet many inquiry-based learning approaches remain insufficiently connected to students’ local cultural contexts, limiting meaningful engagement and knowledge construction. Addressing this gap, this study developed and evaluated a Sasambo-informed Scaffolding Inquiry Model supported by local wisdom-based instructional videos to strengthen scientific literacy among pre-service primary school teachers. A research and development approach based on the ADDIE framework (analysis, design, development, implementation, and evaluation) was employed involving 33 undergraduate students from the Primary School Teacher Education Program at Universitas Muhammadiyah Mataram. The model was refined through expert validation and iterative implementation before being evaluated in classroom settings using observations, questionnaires, and scientific literacy assessments. The findings demonstrate that the proposed model achieved high levels of validity, practicality, and classroom feasibility while substantially improving students’ scientific literacy. Integrating inquiry learning with scaffolding strategies, culturally relevant Sasambo knowledge, and contextual video resources promoted active participation, scientific reasoning, and meaningful connections between scientific concepts and local realities. This study contributes to science education by demonstrating how culturally responsive instructional design can strengthen inquiry learning and scientific literacy in higher education. The proposed model provides a practical framework for integrating indigenous knowledge into science instruction while supporting more contextual and sustainable learning environments.